2021
DOI: 10.3389/fpsyg.2021.643677
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mechanisms in Visual Perception and Their Link With Neural Oscillations: A Review of Evidence From tACS

Abstract: Neurophysiological studies in humans employing magneto- (MEG) and electro- (EEG) encephalography increasingly suggest that oscillatory rhythmic activity of the brain may be a core mechanism for binding sensory information across space, time, and object features to generate a unified perceptual representation. To distinguish whether oscillatory activity is causally related to binding processes or whether, on the contrary, it is a mere epiphenomenon, one possibility is to employ neuromodulatory techniques such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 169 publications
(369 reference statements)
1
20
0
Order By: Relevance
“…This is in line with alphafrequency playing a role in visual and/or attentional sampling (VanRullen and Koch, 2003;VanRullen, 2016;Kienitz et al, 2021). It shows that pre-stimulus alpha-pace may not only impact tasks relying on temporal resolution of visual perception such as temporal integration and segregation (Samaha and Postle, 2015;Wutz et al, 2018;Migliorati et al, 2020; for causal, mostly tACS-evidence see Cecere et al, 2015;Minami and Amano, 2017;Ronconi et al, 2018;Battaglini et al, 2020;Ghiani et al, 2021) but may also impact on perceptual accuracy more generally (Di Gregorio et al, 2022).…”
Section: Introductionsupporting
confidence: 62%
“…This is in line with alphafrequency playing a role in visual and/or attentional sampling (VanRullen and Koch, 2003;VanRullen, 2016;Kienitz et al, 2021). It shows that pre-stimulus alpha-pace may not only impact tasks relying on temporal resolution of visual perception such as temporal integration and segregation (Samaha and Postle, 2015;Wutz et al, 2018;Migliorati et al, 2020; for causal, mostly tACS-evidence see Cecere et al, 2015;Minami and Amano, 2017;Ronconi et al, 2018;Battaglini et al, 2020;Ghiani et al, 2021) but may also impact on perceptual accuracy more generally (Di Gregorio et al, 2022).…”
Section: Introductionsupporting
confidence: 62%
“…Sensory binding refers to this process of melding, and it seems to involve the long-distance synchronisation of the spatially disparate neuronal populations representing the individual features (Bertrand and Tallon-Baudry 2000 ; Ghiani et al. 2021 ). Selective attention is likewise associated with coherence: the cortical neurons representing the attended stimulus produce enhanced, synchronised gamma-band oscillations (Fries 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of these different networks at the source-level might stimulate future transcranial electrical stimulation (tES) studies, in an attempt to bring causal evidence about the role of oscillatory activity within these networks in determining spatio-temporal aspects of perception. In particular, transcranial alternating current stimulation (tACS) could be of central relevance due to its ability to modulate brain oscillations in a frequency-dependent manner, with initial evidence linking tACS at specific frequencies with some basics binding processes in the visual system (for a review see Ghiani et al 2021). Using the two-flash fusion tasks, (Battaglini et al, 2020) showed recently that participants tend to integrate two subsequent flashes more often (i.e., they tend to report just one flash) when 10 Hz tACS (i.e., alpha tACS) was applied over V5/MT of the right hemisphere and surrounding extrastriate visual regions.…”
Section: Discussionmentioning
confidence: 99%